1984
DOI: 10.1116/1.572682
|View full text |Cite
|
Sign up to set email alerts
|

Fracto-emission: The role of charge separation

Abstract: Fracto-emission is the emission of particles (e.g., electrons, ions, ground state and excited neutrals, and photons) during and following fracture. We have found that during fracture in vacuum of adhesive bonds and crystalline materials involving large amounts of charge separation on the surface the emission of charged particles, excited neutrals, light, and radio waves occurs with unique and revealing time dependencies. In this paper we report simultaneous fractoemission measurements on several systems. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…The following high intensity emission event indicates the moment at which the coating fails resulting in a wear trace characterised by both surface cracks and partial delamination (Figure 4b). This is in accordance with previous studies that suggest that emission is due to the high energy generated during the damage of the surface, in particular crack formation [17,19,31,32]. The third region shows relatively few high emission events, occurring due to wearing of the remaining coating.…”
Section: Triboemission Measurementssupporting
confidence: 79%
“…The following high intensity emission event indicates the moment at which the coating fails resulting in a wear trace characterised by both surface cracks and partial delamination (Figure 4b). This is in accordance with previous studies that suggest that emission is due to the high energy generated during the damage of the surface, in particular crack formation [17,19,31,32]. The third region shows relatively few high emission events, occurring due to wearing of the remaining coating.…”
Section: Triboemission Measurementssupporting
confidence: 79%
“…The average angle with the wear track has been found around 60° with a standard deviation of 12. This experimental evidence supports the hypothesis that triboemission occurs due to charge separation resulting from crack formation [18]. This technique of triboemission visualisation by an MCP could provide a powerful tool to visualize crack growth, in real time, giving information on their size and direction.…”
Section: Spatially Resolved Measurementssupporting
confidence: 69%
“…This model however, does not explain why the energy of the tribo-emitted electrons can be lower than the work function of the sample [14]. To account for these low energy electrons, Dickinson et al suggested that the work function of the surface could be locally decreased by small defects in the highly strained areas [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term electromagnetic emission (EME) comprises a wide range of emission effects. This can be electromagnetic radiation directly emitted during and after local mechanical processes, such as fracture [1,2], plastic deformation [3,4] or friction [5,6] as well as the emission of charged particles (sometimes referred to as fracto-emission [7,8]). As sources for the electromagnetic fields, the separation, displacement or movement of bound or free charges are considered.…”
Section: Introductionmentioning
confidence: 99%